Residual acid effect on oxygen delignification - Dos Santos, Rafael [UNESP]; Ventorim, Gustavo [UNESP]; Caraschi, José Cláudio [UNESP] (My University, 2016)
This work has aimed to evaluate the effect of usage of residual acid from the chemical plant of chlorine dioxide production as a #owing part of oxidized white liquor (OWL). Delignification processes were accomplished using as alkali OWL already dosed with residual acid and with NaOH, comparing, thus, the results. Brown stock kraft pulp of eucalyptus industrially produced was used for oxygen delignification accomplishment, being this bleaching stage studied in its particularities according to raw material supplying industry. The oxygen delignification, also named pre-O2, consists of executing previously the bleaching sequence an oxidation of lignin through the oxygen, and subsequently proceeding with these oxidized compounds removal by alkaline media, looking for larger improvements of pulp bleaching this way. The oxygen delignification stages were performed in a Regmed laboratorial reactor provided with four electrically heated capsules. Conditions kept constants were: alkali charge (19 kg/adt), consistency (11%), oxygen pressure (5.8 kgf/cm2), retention time (90 min), initial COD stage (8 kg/adt) and MgSO4 charge (1.5%). The temperature was varied in four different levels (95, 100, 105 and 112°C), and the presence of residual acid in reaction media was also varied. For delignification accomplished at 112°C with NaOH was obtained brightness 62.2%ISO, selectivity 21.7% and delignification efficiency 41.7%. For delignification also at 112°C accomplished with OWL dosed with residual acid was obtained brightness 59.7%ISO, selectivity 20.3% and efficiency 38.6%. The results have evidenced the negative effect of residual acid presence on delignification process, once brightness, selectivity and delignification efficiency were inferior in residual acid presence. Once it has been evidenced its negative effect, it's recommended mix the residual acid with the weak black liquor prior to sending the black liquor to the evaporators, achieving as benefit an interesting chemical balance control without impacting the oxygen delignification stage.
Keywords: Oxidized white liquor; Oxygen delignification